Upaya Peningkatan Kompetensi Guru dalam Mengimplementasikan Pendekatan Saintifik Pada Pembelajaran Di Kelas Melalui Supervisi Klinis - Ahmad Fathullah (Fakultas Pendidikan Islam dan Keguruan Universitas Garut, 2018)
Curriculum 2013 requires teachers to change their mindset and learning patterns. For that, so many trainings and technical guidances organized by spending a lot of money. But very But very unfortunate, generally they are still in the position of 'comfort zone' despite being certified professional educators. The scientific approach is one of the 'icons' of the process standard that requires teachers to be creative in facilitating an active student learning experience, but the reality is not applied. The teacher feels comfortable with the monologue or teacher centered learning. The alternative action that should be immediately given is to conduct a clinical supervision by the supervisor. The focus of clinical supervision is improving the performance of teachers in the classroom. A supervisor provides guidance and service that is collegial and avoids doctrine or suspense. Clinical supervision procedures include pre-observation, class observation and reversal. From the results of the study authors found that this activity can increase the competence of teachers in implementing the scientific approach on learning up to 43%, ie from the initial value of teacher performance in class 41 to 83